High‐Resolution Median Nerve Sonographic Measurements: Correlations With Median Nerve Conduction Studies in Healthy Adults. (1st December 2013) - Marciniak, Christina; Caldera, Franklin; Welty, Leah; Lai, Jean; Lento, Paul; Feldman, Eric; Sered, Heather; Sayeed, Yusef; Plastaras, Christopher
Abstract : Objectives: To study relationships between median wrist and forearm sonographic measurements and median nerve conduction studies. Methods: The study population consisted of a prospective convenience sample of healthy adults. Interventions included high‐resolution median nerve sonography and median motor and sensory nerve conduction studies. Main outcome measures included median motor nerve compound muscle action potential amplitude, distal latency, and conduction velocity; sensory nerve action potential amplitude and distal latency; and sonographic median nerve cross‐sectional area. Median motor nerve and sensory nerve conduction studies of the index finger were performed using standard published techniques. A second examiner blinded to nerve conduction study results used a high‐frequency linear array transducer to measure the cross‐sectional area of the median nerve at the distal volar wrist crease (carpal tunnel inlet) and forearm (4 cm proximally), measured in the transverse plane on static sonograms. The outer margin of the median nerve was traced at the junction of the hypoechoic fascicles and adjacent outer connective tissue layer. Results: Fifty median nerves were evaluated in 25 participants. The compound muscle action potential amplitude with wrist stimulation was positively related to the cross‐sectional area, with the area increasing by 0.195 mm 2 for every millivolt increase in amplitude in the dominant hand (95% confidence interval, 0.020, 0.370 mm 2 ; P < .05) and 0.247 mm 2 in the nondominant hand (95% confidence interval, 0.035, 0.459 mm 2 ; P < .05). There was no significant linear association between the wrist median cross‐sectional area and median motor and sensory distal latencies. Conduction velocity through the forearm was not significantly linearly associated with the forearm area or forearm‐to‐wrist area ratio (tapering ratio). The wrist area was inversely related to the sensory nerve action potential amplitude. Conclusions: Although associations were found between median nerve conduction study amplitudes and sonographic nerve measurements, they were not found for other parameters. Studying these relationships may increase our understanding of when to best use these procedures.